The impacts of animal farming: A critical review of secondary and high school textbooks - Fonseca, R. P. (Cultural Studies of Science Education, 2023)
The exploitation of animals for human purposes raises several ethical concerns in the educational realm that ought to be carefully dealt with. Derived from the content analysis of sample of 39 Portuguese secondary and high school textbooks, this study aims to understand how factory-farmed animals are represented within the following themes: food and health, environment and sustainability, and animal welfare. This work examines whether textbooks suggest the continuation or reduction of the consumption of animal-based products for a healthy diet; discuss the correlation between meat and severe environmental impacts; treat whether plant-based diets are considered healthy, viable and sustainable; and if the agency and welfare of non-human animals is considered. The results show that animals are consistently classified as consumable, with rare mentions of plant-based proteins as a healthy option. Animal farming is inaccurately portrayed as being extensive and is presented from the point of view of maximum production. The suffering and agency of animals are never dealt with. Even though there are some references to the environmental impacts of animal farming, fishing and hunting, there are no recommendations to reduce the consumption of animal-based products as a way of mitigating environmental impacts. The resolution of current environmental challenges is dependent on there being profound shifts in science education that can provide students with the necessary information to create effective change. In seeking to create a more sustainable planet, this study endorses a more ecocentric pedagogy that frames other animals as sentient beings with intrinsic value. It is hoped that the results of this study can motivate authors, reviewers, and scientific and pedagogical consultants to redefine the guidelines in Portugal’s Frame of Reference for Environmental Education, as well the editing criteria for textbooks. Furthermore, this paper seeks to encourage changes in the behaviour of young people and communities towards animals, food and the environment.